Induced differentiation of avian myeloblastosis virus-transformed myeloblasts: phenotypic alteration without altered expression of the viral oncogene. - Symonds, G (1984)
Cells of a clone of avian myeloblastosis virus-transformed myeloblasts were induced to differentiate to adherent myelomonocytic cells by treatment with lipopolysaccharide. These adherent cells were subcultured and maintained as a line for more than 6 months with lipopolysaccharide present. Cells of this line were induced to differentiate to nondividing macrophage-like cells by the addition of the tumor promoter 12-O-tetradecanoylphorbol-13-acetate. In this way, the following homogeneous cell populations representing three distinct stages of myeloid differentiation were obtained: I, actively dividing myeloblasts that grew in suspension: II, actively dividing adherent cells; and III, fully differentiated nondividing cells resembling macrophages. When the expression of v-myb (the oncogene of avian myeloblastosis virus) was examined in cells of these three differentiation stages, it was found that the protein encoded by v-myb (p45v-myb) continued to be synthesized in similar quantities and showed no obvious alteration (assessed by partial proteolytic digestion and two-dimensional gel electrophoresis) during differentiation. These results show that cells transformed by v-myb can be induced to differentiate without affecting the expression of v-myb and imply that, during differentiation, the effect of v-myb is suppressed by a mechanism other than altered expression of the oncogene.